Representasi Perempuan Berkelas Dalam Podcast: Tinjauan Komunikasi Islam - Asyari, M. Khoirul Aqil (Journal of Islamic Communication Studies, 2026)
This study is grounded in the view that digital media, while seemingly promoting gender equality and women’s empowerment, often continues to reproduce symbolic ideologies of femininity and class hierarchy. It aims to analyze the representation of “classy” women in the podcast Suara Berkelas bersama Lavina through the semiotic framework of Roland Barthes and the perspective of Islamic communication. Employing a descriptive qualitative method, the research applies Barthes’ three layers of meaning denotation, connotation, and myth, to examine how verbal and nonverbal signs within the podcast construct images of success and female class identity. Data were drawn from selected episodes, focusing on diction, body gestures, intonation, and Lavina’s visual style as the speaker. The findings indicate that Lavina’s soft, measured, and elegant communication style constructs the image of a “modern successful woman” aligned with urban middle-class values. However, beneath the narrative of empowerment lies a myth of performative equality, wherein women’s success is measured by their ability to conform to dominant social norms. The integration of Islamic communication values siddiq (truthfulness), amanah (trustworthiness), tabligh (conveying truthful messages), and fathanah (wisdom) underscores that effective communication should not merely highlight image or lifestyle but must also convey moral messages and cultural da‘wah that promote equality while safeguarding women’s dignity. Accordingly, this study enriches media semiotics scholarship by incorporating ethical and spiritual dimensions, and it proposes an analytical model that integrates modern communication theory with Islamic values in understanding representational practices within digital spaces.